42nd AIAA Aerospace Sciences Meeting and Exhibit 2004
DOI: 10.2514/6.2004-868
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Flash Vaporization System with Liquid Hydrocarbon Fuels in a Pulse Detonation Engine

Abstract: In recent research, 1,2 liquid fuel droplets were found to hinder the detonation process in a pulse detonation engine (PDE). In the current work, multi-phase effects are eliminated with a flash vaporization system that vaporizes the liquid fuels prior to mixing with air. Hydrocarbon and air mixtures have been transitioned from deflagration to detonations previously, 1 but exhibited long ignition and deflagration to detonation transition (DDT) times. Here, two liquid hydrocarbon fuels, with different octane num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…This research marks the first evaluation of a PDE fueled with thermally and catalytically cracked JP-8 fuel. Previous research 8,9 demonstrated the benefits of preheating JP-8 to flash vaporization and supercritical temperatures. Tucker et al 8 demonstrated that flash vaporization of JP-8 reduces both ignition time and DDT time, as well as increases the ignition and detonation limits.…”
Section: Nomenclaturementioning
confidence: 99%
“…This research marks the first evaluation of a PDE fueled with thermally and catalytically cracked JP-8 fuel. Previous research 8,9 demonstrated the benefits of preheating JP-8 to flash vaporization and supercritical temperatures. Tucker et al 8 demonstrated that flash vaporization of JP-8 reduces both ignition time and DDT time, as well as increases the ignition and detonation limits.…”
Section: Nomenclaturementioning
confidence: 99%
“…The choice of fuel was based on previous single-tube PDE research using a vaporization system where nheptane had short DDT times and detonation speeds consistently at or above the Chapman-Jouguet (C-J) detonation velocity 3 . To avoid the coking that occurs when fuel is heated above 450 K 4 , the oxygen content in the n-heptane was decreased to less than 1 ppm using nitrogen sparging.…”
Section: A Fuelmentioning
confidence: 99%
“…The use of detonation branching as an ignition source with hydrogen fuel has been demonstrated 2 , as has the use of liquid hydrocarbon fuels in a PDE with spark ignition 3 . This paper reports the first attempt at combining the two concepts, i.e., using a branch detonation as an ignition source in a PDE running on liquid hydrocarbon fuel.…”
Section: Introductionmentioning
confidence: 99%
“…1 The need to initiate a new detonation for each cycle of a PDE has led to the development of clever ways to initiate detonations in an alternative to deflagration to detonation transition (DDT) methods. 2 Challenges still remain with improving operating frequency, the time between successive pulse detonations, to levels such that performance surpasses traditional steady state rocket engines. Key experiments in attempting to achieve continuous prolonged PDE operation have shown that repeatable detonation initiation and hardware longevity prove challenging.…”
Section: Introductionmentioning
confidence: 98%